PERBANDINGAN KELAS TERBUKA DAN SESI REFLEKSI DALAM PELAKSANAAN âLESSON STUDYâ DI ANTARA JEPUN DAN MALAYSIA (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract Lesson Study approach is one of the latest effort in improving the quality of education in Malaysia.The success of Lesson Study in Japan has inspired us to adapt this approach according to the education system in Malaysia. By 2015, Malaysia Ministry of Education has implemented the approach through Professional Learning Community (PLC) programme in almost every schoolwith the aimto enhance the quality of education. The learning community gives big impact in lesson study approach by collaboration, discussion and reflection to improve the development of teaching and learning process. Since the implementation of Lesson Study in Malaysia is still at early stage compared to Japan, therefore this article aims to focus on how the implementation of open class and reflection had been carried out in Japan. From the observation of open class and reflection during school visit inJapan, it is found that they have organize a public open class which involved every classes in the school for at least once a year. In addition, a few factors have been identified to enhance the effectiveness of the procedures: a) focused observation, b) complete equipment and team for recording c) committed observer. The reflection session is carried out thoroughly and very detailed.Keywords: Lesson Study approach, Learning Community, Open class, Reflection, Focused observation